A survey of etiologic hypotheses among testicular cancer researchers. (23rd December 2014) - Stang, A.; Trabert, B.; Rusner, C.; Poole, C.; Almstrup, K.; Rajpert‐De Meyts, E.; McGlynn, K. A.
Summary: Basic research results can provide new ideas and hypotheses to be examined in epidemiological studies. We conducted a survey among testicular cancer researchers on hypotheses concerning the etiology of this malignancy. All researchers on the mailing list of Copenhagen Testis Cancer Workshops and corresponding authors of PubMed‐indexed articles identified by the search term 'testicular cancer' and published within 10 years (in total 2750 recipients) were invited to respond to an e‐mail‐based survey. Participants of the 8th Copenhagen Testis Cancer Workshop in May 2014 were subsequently asked to rate the plausibility of the suggested etiologic hypotheses on a scale of 1 (very implausible) to 10 (very plausible). This report describes the methodology of the survey, the score distributions by individual hypotheses, hypothesis group, and the participants' major research fields, and discuss the hypotheses that scored as most plausible. We also present plans for improving the survey that may be repeated at a next international meeting of experts in testicular cancer. Overall 52 of 99 (53%) registered participants of the 8th Copenhagen Testis Cancer Workshop submitted the plausibility rating form. Fourteen of 27 hypotheses were related to exposures during pregnancy. Hypotheses with the highest mean plausibility ratings were either related to pre‐natal exposures or exposures that might have an effect during pregnancy and in post‐natal life. The results of the survey may be helpful for triggering more specific etiologic hypotheses that include factors related to endocrine disruption, DNA damage, inflammation, and nutrition during pregnancy. The survey results may stimulate a multidisciplinary discussion about new etiologic hypotheses of testicular cancer.